Perancangan Ulang Sekolah Luar Biasa Negeri-a Pembina Tingkat Nasional Jakarta Dengan Pendekatan Multisensory Terhadap Mobilitas Tunanetra - Najla Munifa Polem, Cut; Sarihati, Titihan; Puspa Nabila, Ganesha (eProceedings of Art & Design, 2024)
Article 28H stated that citizens have the right to receive special treatment for equality. However, there are still educational gaps, especially for children with disabilities, thus showing that there is still injustice in educational equality. In Indonesia, education specifically for people with disabilities is Special Schools (SLB). Even though we already have SLB, there are still deficiencies in providing education rights services for those with disability status. This is caused by facilities that are considered not in accordance with needs. Existing facilities should be able to accommodate people with disabilities according to their needs. Because of this, a review and redesign are needed with special attention to designing Special Schools (SLB). This statement also applies to State Special Schools – A National Level Pembina Jakarta. The design approach that will be used is multisensory which is related to psychology in the mobility of the blind. Multisensory is a method that has been previously researched and proven to be effective in helping blind children become more independent and skilled in their living environment. This research aims to enable blind people to live independently and can be used as a benchmark in designing Special Schools (SLB) for blind people. Keywords: blind, school for the blind, multisensory.